2015
DOI: 10.1177/1359105315618457
|View full text |Cite
|
Sign up to set email alerts
|

The associations between personality traits, education, occupation and the occurrence of eczema in adulthood

Abstract: There were 5,834 participants with complete data on parental social class at birth, childhood cognitive ability tests scores at 11 years, educational qualifications at 33 years, the Big-FiveFactor personality traits, occupational levels, and eczema ( measured at age 50 years). Results showed that eczema in childhood, educational achievement and occupational levels were significantly associated with the occurrence of reported eczema in adulthood. Emotionally Stable people (non Neurotic) were less likely to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Cheng H. et al [18] found that emotionally stable people were less likely to develop eczema, and in people with sensitivity and openness -dermatosis was more common [15].…”
mentioning
confidence: 99%
“…Cheng H. et al [18] found that emotionally stable people were less likely to develop eczema, and in people with sensitivity and openness -dermatosis was more common [15].…”
mentioning
confidence: 99%